ASUHAN KEBIDANAN KOMPREHENSIF PADA IBU C DENGAN KETUBAN PECAH DINI - Ardania, Ardania; Norisa, Nanda; Asmanidar, Asmanidar; Zahara, Evi; Satrinawati, Satrinawati (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Introduction: The Maternal Mortality Rate (MMR) in Indonesia is still higher compared to ASEAN countries to achieve the SDGs target, which is less than 70 maternal deaths per 100,000 live births in 2030. Early detection efforts to overcome morbidity and mortality for both mothers and babies can be done by implementing continuous care, starting from pregnancy to postpartum without any complications. Objective: This study aims to provide comprehensive midwifery care, especially for pregnant women in the third trimester. Research Method: This study is a case study with a qualitative descriptive approach. The study was conducted by exploring and providing comprehensive midwifery care to Mrs. C G2P0A1, starting from the third trimester of pregnancy to postpartum. This report uses a comprehensive care method, namely collecting data from subjective, objective, determining diagnoses, carrying out management, and documenting in the form of SOAP with supporting documentation in the form of a KIA book. Research Results: Based on the results of midwifery care for mother C, it has been carried out starting from pregnancy care, childbirth, newborns, to postpartum. In pregnancy midwifery care, the first visit found complaints of pain in the lower part and waist area. So that care was carried out by encouraging the mother to do stretching or pregnancy exercises to reduce lower pain and teaching the mother gentle massage techniques to reduce the back pain that the mother felt. On the second visit, the mother had carried out the recommendations given so that the discomfort began to decrease and was resolved by carrying out the recommended recommendations. During childbirth care, the mother said there were no signs of labor even though it had passed the EDD and she felt amniotic fluid seeping from the birth canal. The results of the examination showed an opening of 2, and after there were contractions, the mother could no longer stand the pain. However, after monitoring for 15 hours, there was no progress, so the mother was referred to the hospital and a caesarean section was taken. During newborn care, mother C's baby with a male gender was born by caesarean section. Umbilical cord: brown and not yet dry, skin color: normal, gender: male, normal legs, immediately cries loudly, reddish skin, active muscle tone with an Apgar score of 8, number of toes: 10 fingers, normal back, no swelling, penis: perforated, scrotum: down, anus perforated. In the first postpartum care, The mother complained that her breast milk was coming out a little, so care was given by encouraging the mother to continue breastfeeding her baby as often as possible so that her breast milk would flow smoothly and telling the mother to do breast care such as frequent massage around the breast, maintaining breast cleanliness, and warm compresses on the breast. The blood color was rubra and there were no signs of breast milk dams. At the second postpartum visit, the mother said that she did not feel any complaints, her breast milk had come out, the blood color was sanguinolenta, and her breasts had produced breast milk. Conclusion: Midwifery care provided to mother C, starting from the third trimester of pregnancy to postpartum, can be carried out well using the SOAP method. The results found in the subjective and objective data did not find any gaps, and it was concluded that the analysis and management were in accordance with the theory so that all could be collected